An incremental ramp test for defining training zones in free-swimming - a pilot study - Filho, D.; Vasconcelos, C. M.; de Castro, E. A.; Massini, D. A.; de Almeida, T. F.; Macedo, A. G.; Espada, M. C.; DiMenna, F. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
This study aimed to design a rapidly-incremented protocol to assess peak oxygen uptake (V.O2peak), gas exchange threshold (GET), and respiratory compensation point (RCP) in free swimming. The V.O2max attainment was confirmed, and variables were compared to similar measurements in tethered swimming. Eight male swimmers (19.4±5.2 years, 181.8±8.8 cm and 73.9±10.4 kg) performed two protocols: a ramp-incremental test and a constant bout both in free and tethered swimming. For free swimming, the protocol was 8x100-m stages at 60, 70, 75, 80, 85, 90, 95, 100% of maximal velocity in 200-m. For tethered swimming, a pulley-load system graded workload (WL) increasing at 5% every minute from 30 to 100% of maximum tethered force. The constant bouts for free and tethered swimming were performed at 5% above the highest work rate achieved on each incremental test (i.e., 105% vV.O2peak and WLV.O2peak). Two-way ANOVA analysed the differences (p<=0.05) across conditions (free vs. tethered) and protocols (incremental vs. constant). Correlations were analysed using R2. The were no differences for free vs. tethered swimming for V.O2peak (53.5±6.0 vs. 51.6±5.2 ml kg-1 m n-1), GET (37.2±4.3 vs. 36.1±4.7 ml kg-1 min-1) or RCP (46.3±4.4 vs. 45.9±4.3 ml kg-1 min-1). Moreover, the V.O2max (i.e., the higher values across the two bouts for each swimming mode) did not differ for free vs. tethered swimming (54.9±5.5 vs. 53.0±7.5 ml kg-1 min-1) or when compared to the V.O2peak for each swimming condition. The V.O2peak, and V.O2 at GET and RCP were correlated (R2=0.81, 0.66, and 0.92, respectively); however, the GET and RCP for free swimming (84.2±2.2 and 92.3±3.1 %vV.O2peak) differed (p=0.01) compared to GET and RCP for tethered swimming (68.7±7.9 and 85.8±5.4 %WLV.O2peak). The incremental-ramp test for both free and tethered swimming provides a valid assessment of V.O2peak with values representing the V.O2max. Moreover, GET and RCP (69.6 vs. 69.9 and 86.8 vs. 89.0 %V.O2peak) in free vs. tethered swimming are similar in both swimming conditions, and comparable to previous reports. However, the submaximal mechanical profile (i.e., v or WL at GET and RCP) differed. Hence, submaximal aerobic parameters are mode-specific, and should be assessed in each swimming condition for training planning and performance evaluation (e.g., for sprint pace).